Synthesis, characterization, and properties of high molecular weight poly(methylated ferrocenylsilanes) and their charge transfer polymer salts with tetracyanoethylene - Pudelski, J; Foucher, D; Honeyman, C; Macdonald, P; Manners, I; Barlow, S; OHare, D (1996)
A series of poly(ferrocenylsilanes) with methylated cyclopentadienyl (Cp) rings [Fe(η-C5-MexH4-x)(η-C 5MeyH4-y)SiMe2]n, (2a-e) (a, x = 0, y = 0; b, x = 1, y = 1 (Cp-Me groups at random positions); c, x = 1, y = 1 (Cp-Me groups at 3,3′ positions); d, x = 4, y = 0; e, x = 4, y = 4) have been prepared by thermal ring-opening polymerization (TROP) of the corresponding silicon-bridged [1]ferrocenophanes Fe-(η-C5MexH4-x)(η-C5Me yH4-y)SiMe2 (1a-e). DSC analysis revealed that increasing methylation of the ferrocenophane Cp rings resulted in increasing onset temperatures for the TROP reaction but did not significantly affect the enthalpy of polymerization, ΔHp. Poly(ferrocenylsilanes) 2b-d were soluble in common organic solvents and were characterized by IR, 1H, 13C, and 29Si NMR spectroscopy, and elemental analysis. The molecular weights of these polymers were estimated to be in the range of Mw = 1.8 × 105 to 4.1 × 105 and Mn = 9.4 × 104 to 2.8 × 105 by GPC in THF versus polystyrene standards. The fully methylated poly(ferrocenylsilane) 2e was insoluble in common organic solvents and was characterized by IR, 13C and 29Si CP-MAS NMR, and elemental analysis. The electrochemical behavior of 2b-d in CH2Cl2 solution was investigated by cyclic voltammetry, and these polymers each exhibited two reversible oxidation waves, consistent with significant electronic interactions between the iron centers. Increasing Cp methylation led to the expected decrease in half-wave oxidation potentials, relative to nonmethylated 2a. DSC analysis showed that 2b-d exhibit weak glass transitions which shift to higher temperature with increasing methylation. No melting transitions were detected by DSC for these polymers, and WAXS analysis confirmed that the polymers were amorphous and indicated that the average interchain distance increases with increasing Cp methylation. TGA of 2a-d found decreasing thermal stability with regard to weight loss upon increasing methylation. The microstructure of polymer 2d provided insight into the polymerization mechanism and was consistent with polymerization via nonselective cleavage of Cp-Si (as opposed to Cp-Fe) bonds. The reactions of 2a, 2b, 2d, and 2e with tetracyanoethylene (TCNE) were investigated. Whereas 2a did not react, the Cp-methylated analogues 2b, 2d, and 2e yielded dark solids 3b, 3d, and 3e, which were soluble in polar organic solvents. IR and microanalytical data indicated that the products contain oxidized polymer and a mixture of polycyano counteranions. Bulk solid-state magnetic susceptibility data indicated that 3e obeys the Curie-Weiss law, with μeff = 2.0 μB, and θ = -1.1 K. In contrast to recent reports on TCNE-oxidized oligo(ferrocenylsilanes), no evidence was found for any long-range cooperative spin-spin interactions at low temperature.